2004
DOI: 10.1160/th04-04-0206
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of a factor Xa inhibitor YM466 and a GPIIb/IIIa antagonist YM128 on thrombosis and neointima formation in mice

Abstract: SummaryThrombosis and neointima formation limit the efficacy of coronary angioplasty. Factor Xa inhibitors and GPIIb/IIIa antagonists have shown to be effective on acute thrombosis and late neointima formation, however, their combined effects remain to be elucidated. Vascular injury was induced by FeCl3 in the carotid artery in mice. For thrombosis studies, the test drug was orally administered 1 hour before vascular injury. For neointima studies, the test drug was orally administered 1 hour before and twice d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
3
13
0
Order By: Relevance
“…So far, the ferric chloride induced injury model has been used to study the impact of pharmacologic interventions using anti-thrombotic/anti-coagulant test compounds and evaluating their capability to delay time to occlusion or to prevent occlusion [18][19][20][21][22][23]. Previously it was demonstrated that no occlusion of carotid artery [33][34][35] and mesenteric venules [36] was observed following FeCl 3 induced injury in F8-KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the ferric chloride induced injury model has been used to study the impact of pharmacologic interventions using anti-thrombotic/anti-coagulant test compounds and evaluating their capability to delay time to occlusion or to prevent occlusion [18][19][20][21][22][23]. Previously it was demonstrated that no occlusion of carotid artery [33][34][35] and mesenteric venules [36] was observed following FeCl 3 induced injury in F8-KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…37 Prolonged times to occlusion were observed in mice deficient in fIX, 53 fXI, 53 or fXII. 35 Also, inhibitors of thrombin, 54 fIXa, 55 or fXa 56 prolonged times to occlusion in WT mice after FeCl 3 injury. Inhibitors of specific platelet receptors also prolonged the time to occlusion; these included inhibitors of glycoprotein VI (GPVI), 57 ␤ 3 , 58 P2Y 12 , 59 or P2Y 1 59 (but not P2X 1 59 ).…”
Section: Ferric Chloridementioning
confidence: 98%
“…Inhibitors of specific platelet receptors also prolonged the time to occlusion; these included inhibitors of glycoprotein VI (GPVI), 57 ␤ 3 , 58 P2Y 12 , 59 or P2Y 1 59 (but not P2X 1 59 ). Modulation of platelet signaling molecules, such as phosphatidylinositol 3-kinase␥, 60 phospholipase C␤, 60 Rap1b, 61 or p38␣ 62 (by P2Y 12 63 or ␣ IIb ␤ 3 antagonists 56,64 ) also prolonged the time to occlusion. These data further support the important role that collagen and thrombin play in carotid artery occlusion after FeCl 3 injury.…”
Section: Ferric Chloridementioning
confidence: 99%
“…By contrast, the thrombus area on collagen was evidently higher in homo platelets, which could be attributed to the defects in retraction of platelet aggregates in homo mice (Figure S2). Moreover, ferric chloride‐induced arterial thrombosis was highly impaired in homo mice (Figure D). Taken together, the above findings indicated that platelet function is markedly impaired in homo mice, consistent with the marked αIIbβ3 reduction in homo platelets.…”
Section: Resultsmentioning
confidence: 99%
“…Mouse tail bleeding time was determined as previously described . Briefly, tails of 8‐ to 9‐week‐old male mice were transected 2 mm from the tip.…”
Section: Methodsmentioning
confidence: 99%